2005
DOI: 10.1029/2005ja011263
|View full text |Cite
|
Sign up to set email alerts
|

Plasmoids observed in the near‐Earth magnetotail at X ∼ −7 RE

Abstract: [1] Recent studies have statistically shown that the magnetic reconnection site at substorm expansion onset is located in the magnetotail at X $ À20 R E on average. For a substorm event that occurred at $0153 UT on 2 July 1996, however, Geotail observed a series of tailward but slow flows with southward magnetic fields fairly close to the Earth at (X, Y) $ (À7, 9) R E . The flows had enhancements of the total pressure and the total magnetic field as well as bidirectional field-aligned low-energy electrons in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 57 publications
3
13
1
Order By: Relevance
“…In contrast with previously discussed observations of tailward fast flows in the near-Earth magnetotail (Nagai et al, 1998a;Eriksson et al, 2004;Miyashita et al, 2005), these three flow bursts were observed during northward IMF. IMF B z was northward (of 5-10 nT) during ∼2.5 h before the first tailward flow was observed.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In contrast with previously discussed observations of tailward fast flows in the near-Earth magnetotail (Nagai et al, 1998a;Eriksson et al, 2004;Miyashita et al, 2005), these three flow bursts were observed during northward IMF. IMF B z was northward (of 5-10 nT) during ∼2.5 h before the first tailward flow was observed.…”
Section: Discussioncontrasting
confidence: 53%
“…Their appearance implies either enhanced magnetic activity (e.g. Miyashita et al, 2005;Nagai et al, 2005) or a mechanism that differs from acceleration at a NENL (e.g. Schödel et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the presence of the X-line location closer to the Earth has been shown in different studies; e.g., Petrukovich et al (2009) estimated the x GSM ∼ −17 R E from the Cluster survey in the 11-20 R E region in the tail. From case studies using multi-spacecraft conjunctions, the near-Earth X-line position is obtained at x GSM ∼ −7 R E (Miyashita et al, 2005), in the range between ∼9-10 to ∼13-14 R E and ∼10-12 R E . One of the probable causes of the discrepancy in the X-line location is suggested to be in the various solar wind conditions before substorm onset .…”
Section: A Alexandrova Et Al: Remote Estimation Of Reconnection Parmentioning
confidence: 99%
“…Requiring no reconnection, these waves produce the same twin signature in the plasma sheet/PSBL (plasma sheet boundary layer) or in the lobes: the bipolar B z -variation plus the B x -compression (Lee et al, 1988;Miyashita et al, 2005;Takada et al, 2005).…”
Section: Introductionmentioning
confidence: 99%